Green tea polyphenol sensing - TACHIBANA, Hirofumi (The Japan Academy, 2011)
Green tea polyphenols have emerged over the past two decades as an important dietary factor for health promotion. There is considerable evidence that tea polyphenols, in particular (−)-epigallocatechin-3-gallate (EGCG) inhibit carcinogenesis. However, the mechanisms for the cancer-preventive activity of EGCG are not completely characterized and many features remain to be elucidated. Recently we have identified a cell-surface EGCG receptor and the relating molecules that confer EGCG responsiveness to many cancer cells at physiological concentrations. Here, we review some of the reported mechanisms for the cancer chemopreventive action of EGCG and provide an overview of several molecules that sense and manage the physiological functions of EGCG.